A synteny‐based draft genome sequence of the forage grass Lolium perenne. (November 2015) - Byrne, Stephen L.; Nagy, Istvan; Pfeifer, Matthias; Armstead, Ian; Swain, Suresh; Studer, Bruno; Mayer, Klaus; Campbell, Jacqueline D.; Czaban, Adrian; Hentrup, Stephan; Panitz, Frank; Bendixen, Christian; et al.
Summary: Here we report the draft genome sequence of perennial ryegrass ( Lolium perenne ), an economically important forage and turf grass species that is widely cultivated in temperate regions worldwide. It is classified along with wheat, barley, oats and Brachypodium distachyon in the Pooideae sub‐family of the grass family (Poaceae). Transcriptome data was used to identify 28 455 gene models, and we utilized macro‐co‐linearity between perennial ryegrass and barley, and synteny within the grass family, to establish a synteny‐based linear gene order. The gametophytic self‐incompatibility mechanism enables the pistil of a plant to reject self‐pollen and therefore promote out‐crossing. We have used the sequence assembly to characterize transcriptional changes in the stigma during pollination with both compatible and incompatible pollen. Characterization of the pollen transcriptome identified homologs to pollen allergens from a range of species, many of which were expressed to very high levels in mature pollen grains, and are potentially involved in the self‐incompatibility mechanism. The genome sequence provides a valuable resource for future breeding efforts based on genomic prediction, and will accelerate the development of new varieties for more productive grasslands. Significance Statement: Perennial ryegrass (Lolium perenne) is an economically important forage and turf grass species cultivated worldwide in temperate regions. The genome sequence provides a valuable resource for molecular breeding efforts and will accelerate variety development for more productive grasslands.